Social accounting matrices for Vietnam 1996 and 1997 - Pohl Nielsen, Chantal (International Food Policy Research Institute, 2002)
This paper documents the construction of social accounting matrices (SAMs) for Vietnam for 1996 and 1997. The data sources used to construct the SAMs include national accounts statistics, government budget data, the official 1996 input-output table, the 19 97/98 Vietnam Living Standards Survey (VLSS), and COMTRADE trade data. The agri- food sectors are particularly well represented in the SAMs: the resulting VIETSAM includes 97 producing sectors with eight agricultural sectors, two agricultural service sectors and 13 food processing industries. In terms of institutional detail, the SAMs include five factors of production (three types of labor distinguished by skill level, one type of capital and one type of land), six household types (distinguished by rural/urban, agricultural/non-agricultural, wage/self-employed), and one account each for enterprises, government, investment/savings and rest-of-world. The rest-of-world account is a purely non-trade-related account that keeps track of financial transfers between Vietnamese institutions and the rest of the world. This is because the innovative feature of this SAM is that is takes detailed account of Vietnam’s foreign trade flows. Imports and exports of goods and services are distinguished by trading partner – more specifically, 94 partner countries are identified. The SAM is estimated using a cross-entropy approach, which makes efficient use of all available data whilst at the same time allowing for the incorporation of prior information and constraints.